Media Trial in the New Media Era From the Perspective of the Cargo Lala Incident (Asian Journal of Social Science Studies, 2022)
With the development of web2.0 era, the audience's right to speak has played an increasingly important role in communication activities. Since the we-media emerged in endlessly, everyone can spread something. This has led to many media ethics problems, a large part of which is media trial. This article will be based on the “Cargo Lala Incident” and analyze the media trial.